Response of BALB/c mice to a monovalent influenza A (H1N1) 2009 split vaccine - Yang, Penghui (Nature Publishing Group, 2010)
The novel influenza A (H1N1) 2009 virus has emerged to cause the first pandemic of the twenty-first century. Disease outbreaks caused by the influenza A (H1N1) virus have prompted concerns about the potential for a pandemic and have driven the development of vaccines against this subtype of influenza A. In this study, we developed a monovalent influenza A (H1N1) split vaccine and evaluated its effects in BALB/c mice. Mice were immunized subcutaneously with 2 doses of the vaccine containing hemagglutinin (HA) alone or HA plus an aluminum hydroxide (Al(OH)(3)) adjuvant. Immunization with varying doses of HA (3.75, 7.5, 15, 30, 45 or 60 µg) was performed to induce the production of neutralizing antibodies. The vaccine elicited strong hemagglutination inhibition (HI) and microneutralization, and addition of the adjuvant augmented the antibody response. A preliminary safety evaluation showed that the vaccine was not toxic at large doses (0.5 ml containing 60 µg HA+600 µg Al(OH)(3) or 60 µg HA). Moreover, the vaccine was found to be safe at a dose of 120 µg HA+1200 µg Al(OH)(3) or 120 µg HA in 1.0 ml in rats. In conclusion, the present study provides support for the clinical evaluation of influenza A (H1N1) vaccination as a public health intervention to mitigate a possible pandemic. Additionally, our findings support the further evaluation of the vaccine used in this study in primates or humans.